Influence of titanium oxide-based colourants on the morphological and tribomechanical properties of injection-moulded polyoxymethylene spur gears - Schubert, Dominik; Hertle, Sebastian; Drummer, Dietmar (Journal of Polymer Engineering, 2019)
Regardless of colouration for functional or aesthetic purposes, technical polymer parts, like gears, require consistent properties. However, there is a lack of research into the effect of colourants on the tribomechanical properties of gears. Therefore, the effects of two pigments, titanium dioxide (white) and chrome antimony titanium oxide (yellow), and three delivery methods, masterbatch, liquid colour and direct compounding, on part morphology, dimensions, tribological and mechanical performance of injection-moulded polyoxymethylene (POM) spur gears are investigated in this paper. The white pigment accelerates the crystallisation of POM, causing fine and highly-crystalline morphological structures and smaller dimensions. However, the yellow pigment decelerates crystallisation, resulting in a coarser morphology with highly crystalline core material and bigger parts. Furthermore, the delivery method affects only the tribomechanical properties. Using a masterbatch decreases loads at break and increases deflection at break, since the carrier material acts as an impact modifier and a weak spot. The liquid colour decreases wear due to lubricating properties, whereas the pure pigments increases abrasion, especially in combination with a coarse microstructure. However, the effects of carrier systems and changes in morphology are always superimposed. Considering the performance and tolerance of technical components, colourants have to be carefully selected to ensure beneficial properties.
CRIS-Team Scopus Importer:2019-08-16
Keywords: colouration; nucleation; polymer gears; tribology; wear